Implementing Samarinda City Spatial Planning Policy Toward a Civilized and Sustainable City - Ema Karisma Wati; Enos Paselle; Saipul (University of Merdeka Malang, 2026)
Spatial planning is crucial for sustainable development in rapidly growing cities. However, in Samarinda City, widespread land-use violations and weak control over spatial utilization threaten the effectiveness of spatial planning policies in achieving the city's long-term goals. To unravel this complexity, this study contributes a novel theoretical integration—combining the frameworks of Van Meter and Van Horn with those of Mazmanian and Sabatier—to analyze the Spatial Planning (RTRW) policy in the context of realizing a civilized and sustainable city. The RTRW policy, often fraught with political interests and characterized by rigidity, requires a collaborative theoretical approach to bridge gaps and resolve communication issues regarding strategies, policy characteristics, and the roles of multiple stakeholders. Consequently, this framework serves as an integrated analytical tool to assess the extent of change and the impact of RTRW policy implementation. Qualitative approach based on a single case study with a purposive sampling method involving five members of the Spatial Planning Forum (FPR) representing various agencies and institutions, as well as local executive and legislative officials based on field data (observations and interviews) and supplementary information. The data were interpreted using Creswell’s spiral analysis model, supported by NVivo 12 software. The successful realization of the RTRW policy for a civilized and sustainable city is evidenced by implementer compliance, the minimization of sectoral ego, and the effective accommodation of spatial planning interests. This success is manifested in several areas: the sustainable economic aspect is demonstrated by the integration of economic zones that stimulated an 8.66% increase in Locally-Generated Revenue (PAD) without compromising the provision of public open spaces and RTH. Similarly, regarding law enforcement and violation resolution, decisive actions have been taken, such as regulatory measures to phase out oil palm plantation areas and restrict coal mining business licenses (IUP) starting in 2026.